Sarcoma de Kaposi asociado a no VIH: A propósito de un caso - Joana Fontes; Tiago Mendes; Joana Silva; Bárbara Sousa (Sociedade Galega de Medicina Interna, 2022)
Kaposi sarcoma (KS), first described in 1872, is a angioproliferative neoplasm that often presents with red-purple macules in the skin. This report is of a case of classic/iatrogenic form of KS in a 79-year-old male, that had a prolonged hospitalization due to surgical complications. After discharge, he presented a red-purple macule. A biopsy was made and KS was confirmed. He was HIV negative. The patient did not required any other treatment asides of total removal of the lesion. Kaposi's sarcoma is an uncommon disease, still very associated with HIV. This case demonstrates the importance of recognition of KS in non-HIV patients. There are four types of Kaposi's sarcoma and the importance of its recognition in non-HIV patients.